Blind Sonar Sebagai alat Bantu Berjalan Bagi Penyandang Tuna Netra - Indra Darmawan Budi; Adi Asmariadi Budi (Inovasi Pembangunan : Jurnal Kelitbangan, 2015)
Blind sonar is a tool which especially designedto help people who suffer blindness, so with it they can navigate on walking. Blind sonaris working with a principal of distance sensor like a natural sensor of a bat, which is designed using ultrasonic sensor SRF 04. This blind sonar usetwo distance sensors which appliedon the device, one of it is located on top, and the other one is located in front of the device. The front distance sensor is used for detecting an obstacles like a hole, broken way or even a big stone on their way. When the sensor detecting an obstacle, it will turn on the small motor, and it will give a vibration which will be felt on the hand of the user. This vibration will indicate that there is obstacle in front of the user, like a hole, broken road or a stone. The top distance sensor is used to indicate an obstacle in top area, like a branch of tree,the edge of the door or the window. The vibration sign will give a navigation to the blind people to navigate on walking. The hopeis that blind sonar can give a best response from detecting any obstaclefor a blind people, so the user can move and walk around freely and safely from any danger of obstacleon their way’